Extraction of Chromium(VI) From Aqueous Solution by Liquid Surfactant Membrane - Frites, M.; Samar, M.H.; Boutefnouchet, N.; Abbaci, A. (Asian Journal of Chemistry, 2016)
The extraction of chromium(VI) through a liquid surfactant membrane with tri-butylphosphate and tri-octylphinoxide dissolved in dodecane considered as a carrier, was investigated. Tri-ethanolamine was used as inner phase reagent. The effects of the reaction time, pH of external phase, the concentration of extractant in the organic phase, the inner phase concentration and the Cr(VI) concentration in aqueous solution were also investigated. The extraction of Cr(VI) increases with the increase of external phase pH. This study has revealed that there exists an optimal range of tri-octylphinoxide concentrations added to tri-butylphosphate in the membrane phase where a maximum metal extraction can be achieved. The complexes H2CrO4(TBP)2 and H2CrO4(TOPO)2 formed in the membrane phase are proposed to describe the transport of Cr(VI); the interfacial interaction organic phase-inner phase including the equilibria among H2CrO4(TBP)2, H2CrO4(TOPO)2, OH–, (CrO42−)aq, 2(TOPO)org, 2(TBP)org and H2O are proposed to describe the striping of Cr(VI).